Iraqi Tourism Information Resources (ITIR) - Asmail, Mohammed A. Ahmed (2011)
Iraq has been suspected to have weapons of mass destruction and thus have war with America for many years. This war build a very horrible image of this country but actually, there is no so-called "weapon of mass destruction" found after seven years. It is time for the American to withdraw its army from Iraq and also time for the public to know the real Iraq. Thus, this study will built an Iraq tourism website called the Iraqi Tourism Information Resources (ITIR) using Web 2.0 to boost the tourism industry in Iraq because Tourism Industry is very important for the Iraq to rebuild its international image and generate the income to help rebuild its economy after the war. Waterfall methodology was used in this study.